Vagal innervation is required for the formation of tertiary lymphoid tissue in colitis. Issue 10 (18th August 2016) - Olivier, Brenda J.; Cailotto, Cathy; van der Vliet, Jan; Knippenberg, Marlene; Greuter, Mascha J.; Hilbers, Francisca W.; Konijn, Tanja; te Velde, Anje A.; Nolte, Martijn A.; Boeckxstaens, Guy E.; de Jonge, Wouter J.; Mebius, Reina E.
Abstract : As a result of inflammation, resting stromal cells in the colon become activated and upregulate chemokines (CXCL13, CCL20 and CCL19) and adhesion molecules (VCAM and MadCAM) that attract and maintain B‐ and T‐lymphocytes to the inflamed area, leading to the formation of tertiary lymphoid tissue (TLT). Vagal nerve activity is critical in the ability of stromal cells to upregulate CXCL13 and CCL20. Without vagal innervation to the inflamed area, stromal cells fail to upregulate CXCL13 and CCL20, and TLT does not form. Abstract : Tertiary lymphoid tissue (TLT) is lymphoid tissue that forms in adult life as a result of chronic inflammation in a tissue or organ. TLT has been shown to form in a variety of chronic inflammatory diseases, though it is not clear if and how TLT develops in the inflamed colon during inflammatory bowel disease. Here, we show that TLT develops as newly formed lymphoid tissue in the colon following dextran sulphate sodium induced colitis in C57BL/6 mice, where it can be distinguished from the preexisting colonic patches and solitary intestinal lymphoid tissue. TLT in the inflamed colon develops following the expression of lymphoid tissue‐inducing chemokines and adhesion molecules, such as CXCL13 and VCAM‐1, respectively, which are produced by stromal organizer cells. Surprisingly, this process of TLT formation was independent of the lymphotoxin signaling pathway, but rather under neuronal control, as we demonstrate that selective surgical ablation of vagus nerve innervation inhibits CXCL13 expression and abrogates TLT formation without affecting colitis. Sympathetic neuron denervation does not affect TLT formation. Hence, we reveal that inflammation in the colon induces the formation of TLT, which is controlled by innervation through the vagus nerve.